A Cell-Based Renilla Luminescence Reporter Plasmid Assay for High-Throughput Screening to Identify Novel FDA-Approved Drug Inhibitors of HPV-16 Infection. (January 2020) - Walhart, Tara; Isaacson-Wechsler, Erin; Ang, Kean-Hooi; Arkin, Michelle; Tugizov, Sharof; Palefsky, Joel M.
Like cervical cancer, anal cancer is caused by human papillomavirus (HPV). HPV is the most common sexually transmitted agent and is found in the anal canal of almost all HIV-positive men who have sex with men (MSM). Rates of HPV anal cancer are disproportionately higher in this population. Although the nanovalent HPV vaccine is efficacious in protecting against oncogenic HPV types, a substantial proportion of MSM remains unvaccinated and anal HPV infection continues to be an important public health burden. Therefore, it is important to identify strategies to prevent HPV infection. We report on two promising and interlinked strategies: (1) the development of a cell-based Renilla luminescence reporter assay using HPV-16 pseudovirions that encapsidate SV40-driven Renilla luminescence reporter expression plasmid and (2) use of this assay for high-throughput screening (HTS) of FDA- and internationally approved drugs to identify those that could be repurposed to prevent HPV infection. We conducted a screen of 1906 drugs. The assay was valid with a Z′ of 0.67 ± 0.04, percent coefficient of variance of 10.0, and signal-to-background noise window of 424.0 ± 8.0. Five drugs were chosen for further analyses based on selection parameters of ≥77.0% infection of HPV-16 pseudovirion-driven Renilla expression with <20.0% cytotoxicity. Of these, the antifungal pentamidine and a gamma-amino butyric acid receptor agonist securinine exhibited ≥90.0% infection with <10.0% cytotoxicity. This luminescent cell-based reporter expression plasmid assay for HTS is a valid method to identify FDA- and internationally approved drugs with the potential to be repurposed into prevention modalities for HPV infection.